073 Evaluation of clinical markers of early disease expression and the ability to predict genotype in families with HCM and mutations in cardiac myosin binding protein C. (16th May 2012) - Page, S P; Kounas, S; Syrris, P; Christiansen, M I; Rune-Hansen, F; Andersen, P S; Elliott, P M; McKenna, W J
Abstract : Introduction: Familial evaluation for the presence of left ventricular hypertrophy (LVH) is an important part of management in hypertrophic cardiomyopathy. However due to incomplete penetrance, the presence of LVH does not reliably identify all mutation carriers, with consequences for cascade screening. Previous studies in small genotyped populations have suggested that reduced myocardial tissue Doppler velocities in unaffected relatives may predate the development of LVH and may therefore be useful in identifying at risk relatives. The value of such techniques in a large cohort of genotyped relatives remains unknown however. This study sought to prospectively evaluate ECG and Echo markers of early disease expression in a large genotyped cohort of families with mutations in myosin binding protein C (MYBPC3). Methods: Relatives of index cases with HCM related to mutations in MYBPC3 (4 insertion/deletion, 7 missense, 4 nonsense, 5 intronic, 2 double heterozygotes) were evaluated. Clinical examination, ECG and transthoracic Echo (operator blinded to genetic status) were performed and combined with genetic predictive testing. The clinical value of ECG and Echo derived indices in predicting genotype were assessed. Results: Of 95 relatives, 40 did not carry the family mutation (Group 1, 22 males, 38.5±16.7 years), 39 were unaffected mutation carriers (Group 2, 17 males, 37.4±16.8 years) and 16 were clinically affected and excluded from the study. ECG evidence of left atrial enlargement (21 vs 3%, p=0.01) and non-pathological Q waves (64 vs 28%, p=0.001) were more common in group 2 than group 1. S wave amplitude in lead V2 was greater in group 2 than group 1 (16.6±7.9 vs 12.4±8.2 mV, p=0.02) and also lead V3 (12.7±6.9 vs 9.3±6.1 mV, p=0.02). ECG criteria for left ventricular hypertrophy were specific but not sensitive for identifying mutation carriers (Abstract 073 table 1 ). Lateral annular late diastolic velocities were increased in group 2 but all other tissue Doppler indices were similar between the two groups (Abstract 073 table 2 ). The proposed cut-off values (from previous studies) were tested in our larger study and found to be clinically unhelpful; lateral Ea velocity <14 (sensitivity 40%, specificity 50%), lateral Sa velocity <13 (sensitivity 50%, specificity 50%), septal Sa <12 (sensitivity 100%, specificity 0%) and septal Ea <13 (sensitivity 70%, specificity 30%). Conclusions: In previous small studies, tissue Doppler indices have been reported to be both sensitive and specific for identifying unaffected mutation carriers. However in our larger study, tissue Doppler imaging was unhelpful in predicting genotype and with current imaging techniques it is not possible to reliably identify unaffected mutation carriers before the development of ventricular hypertrophy.